Balancing antimicrobial activity with biological safety: bifunctional chitosan derivative for the repair of wounds with Gram-positive bacterial infections. Issue 23 (29th May 2018) - Zhu, Meng; Liu, Peng; Shi, Haigang; Tian, Ye; Ju, Xiaoyan; Jiang, Shidong; Li, Zhuang; Wu, Man; Niu, Zhongwei
Abstract : Because of the balance between antimicrobial activity and biological safety, the bifunctional chitosan derivative could control infections and promote healing simultaneously. Abstract : Infection control and the promotion of healing are two key factors during the wound repair process. However, it is still a major challenge for one material to inhibit bacterial growth efficiently and promote wound healing at the same time. Here, a bifunctional chitosan derivative (CS-G/mPEG) was prepared by the successive modification of chitosan with carboxymethoxypolyethylene glycol (mPEG-COOH) and aminoiminomethanesulfonic acid (AIMSOA). We demonstrated that CS-G/mPEG can selectively disrupt bacterial membranes with high efficiency and thus kill Gram-positive bacteria without inducing hemolysis or cytotoxicity. In rats with full-thickness skin wounds infected with Staphylococcus aureus bacteria, CS-G/mPEG inhibited the growth of the bacteria and accelerated the healing of the wounds. Owing to the balance between the antimicrobial activity and biological safety of CS-G/mPEG, this bifunctional chitosan derivative is promising as an ideal anti-infective wound-repairing material for managing wounds with Gram-positive bacterial infections.